Initial growth of white ipê (Handroanthus roseoalbus (Ridl.) Mattos) under three light intensities (Research, Society and Development, 2021)
The production of seedlings in quantity and quality is one of the most important steps in the process of implementing forest stands. To be successful in the nurseries, factors such as the type of substrate, container volumes, type of fertilization, temperature and luminosity need to be known. The objective of this work was to evaluate the initial development of white ipe seedlings under different light gradients. The experiment was carried out in the city of Rio Branco, Acre, in a completely randomized design, with three treatments and ten replications. The treatments were full sun production, with 50% and 70% shading. Plant height, stem diameter, shoot dry mass, root dry mass, and total dry mass were evaluated, in addition to the Dickson quality index. It was found that the white ipe seedlings develop properly in full sun environment, where the seedlings with the best quality indicators are obtained.